Influencia de las canciones infantiles como mediadoras del desarrollo del lenguaje oral en los niños y niñas de 4 a 5 años de la Unidad Educativa Provincia de Los Ríos de la parroquia Barbones, del cantón El Guabo, en el período lectivo 2013-2014. - López Jiménez, Maricela Patricia (2014)
Children's songs are rhythmic expressions that awaken the curiosity of their environment in children, facilitating the assimilation and construction of their knowledge, so that in the programming of an educator should not miss these instruments and should not be replaced by other resources , As these are important manifestations and each has its place in education.